Exploring the university partnership model for child welfare citizen review panels: A research brief. (October 2017) - Miller, J. Jay; Collins-Camargo, Crystal; Jones, Blake
Abstract: Child Welfare Citizen Review Panels (CRPs) are groups of citizen volunteers authorized by Child Abuse Prevention and Treatment Act (CAPTA; P.L. 104-235) to examine practices of public child welfare agencies. Increasingly, state CRP groups are engaging in university-community partnerships to assist in meeting CAPTA mandates. Despite this trend, there are no published studies that examine this practice. This research brief examines group differences between CRP members of university and non-university affiliated panels, respectively. Factors of interest included CRP Knowledge, Member Satisfaction, Member Engagement, Personal Influence, Perceived CRP Impact on Child Welfare System, CRP Member Dynamics, and Meeting Format. Results indicate that respondents perceived themselves to be no more knowledgeable or engaged in their panels and expressed no greater confidence in the potential impact of CRPs on the child welfare system, whether affiliated with a university or not. After a brief review of literature, this brief will explicate findings derived from this study and discuss salient implications and areas for future research. Highlights: Increasingly, state CRP groups are engaging in university-community partnerships to assist in meeting CAPTA mandates. This research brief examines group differences between CRP members of university and non-university connected panels. Results indicate no differences between university-affiliated and non-university-affiliated CRPs.